Power Quality Consideration for Off-Grid Renewable Energy Systems - Hojabri, Mojgan; Toudeshki, Arash (Scientific Research, 2013)
Necessity of electricity access in remote area is the main reason for expanding decentralized energy system such as stand-alone power systems. The best electrical power supply must provide a constant magnitude and frequency voltage. Therefore, good power quality is an important factor for the reliable operation of electrical loads in a power system. However, the current drawn by most of electronic devices and non-linear loads are non-sinusoidal, which can result in a poor power quality, especially in off-grid power systems. Poor power quality is characterized by electrical disturbances such as transients, sags, swells, harmonics and even interruptions in the power supply. Off-grid power systems world- wide often struggle with system failures and equipment damage due to poor power quality. In this paper, MAT- LAB/Simulink is used to model and analyses power quality in an off-grid renewable energy system. The results show high voltage transient when the inductive loads were switched OFF. The voltage and current harmonics are also deter- mined and compared for various types of loads.